2015
DOI: 10.1117/1.jbo.20.2.025006
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of rabbit brain in the red and near-infrared: changes observed underin vivo, postmortem, frozen, and formalin-fixated conditions

Abstract: The outcome of light-based therapeutic approaches depends on light propagation in biological tissues, which is governed by their optical properties. The objective of this study was to quantify optical properties of brain tissue in vivo and postmortem and assess changes due to tissue handling postmortem. The study was carried out on eight female New Zealand white rabbits. The local fluence rate was measured in the VIS/NIR range in the brain in vivo, just postmortem, and after six weeks' storage of the head at −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
5
27
1
Order By: Relevance
“…The spectral trend of μ s mirrors that of μ a , where μ s decays slowly with increasing wavelength as expected due to the increased mie scattering relative to Rayleigh scattering . Similar to μ a , the differences between healthy and diseased tissue is evident.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The spectral trend of μ s mirrors that of μ a , where μ s decays slowly with increasing wavelength as expected due to the increased mie scattering relative to Rayleigh scattering . Similar to μ a , the differences between healthy and diseased tissue is evident.…”
Section: Resultssupporting
confidence: 65%
“…The integrating sphere measurements showed that tissue optical properties from non‐cancerous tissue differed from those of cancerous ones across the whole spectral range. All three optical properties, μ a , μ s and g, were consistently higher in the tumor samples, as also observed in vivo . Specifically, pleomorphism, the presence of densely packed chromatin and necrotic tissue all contribute to enhanced scattering, where the scatter centers (nuclei and organelles) are larger in size, more heterogeneous and more abundant in tumors compared to non‐tumorigenic cells .…”
Section: Discussionmentioning
confidence: 99%
“…Another factor influencing the optical property is the ex vivo tissue preparation. Overall, tissue dehydration increases scattering probably due to more dense packing of the intercellular and intracellular components, and the crosslink of proteins during fixation is likely to change the scattering property as well [30,31]. There is a general negative correlation between the scattering coefficient and the AIP, as expected as the greater light attenuation results in a lower average intensity in the OCT images.…”
Section: Optical Properties Of the Human Brainmentioning
confidence: 50%
“…7). In addition, since fixation typically increases the scattering coefficient of tissue26, it is expected that this penetration depth represents a lower bound; live tissues will have lower scattering coefficients and larger penetration depths, as demonstrated by Begue et al 27. who managed to project two-photon temporal focusing patterns through a 550-μm-thick live brain slice, albeit using a longer wavelength (950 nm) and coarser features (on the order of 10 μm) than tested here.…”
Section: Resultsmentioning
confidence: 99%